Selective inhibition of histone deacetylase 8 improves vascular hypertrophy, relaxation, and inflammation in angiotensin II hypertensive mice - Kee, Hae Jin (Clin Hypertens, 2019)
BACKGROUND: The dysregulation of histone deacetylase (HDAC) protein expression or its enzyme activity is implicated in a variety of diseases. Cardiac HDAC6 and HDAC8 enzyme activity induced by deoxycorticosterone acetate (DOCA) hypertension was attenuated by sodium valproate, a pan-HDAC inhibitor. However, the HDAC6-selective inhibitor, tubastatin A, did not attenuate angiotensin II-induced hypertension. The purpose of this study was to investigate whether PCI34051, an HDAC8-selective inhibitor, can modulate angiotensin II-induced hypertension and its regulatory mechanism. METHODS: An angiotensin II-regulated mouse model was used in this study. Animals received vehicle or PCI34051 (3 mg·kg − (1)·day− (1)) via intraperitoneal injection. Systolic blood pressure was measured by the tail-cuff method. Blood vessel thickness was measured following hematoxylin and eosin staining, VCAM-1 immunohistochemistry was performed in the aortas, and mRNA expression of renin-angiotensin system components, inflammation markers, and NADPH oxidase (Nox) was determined by RT-PCR. The effect of PCI34051 on vasorelaxation was studied in rat aortic rings, and its effect on nitric oxide (NO) production was determined using DAF-FM DA, a fluorescent dye, in human umbilical vascular endothelial cells (HUVECs). RESULTS: PCI34051 administration reduced systolic blood pressure via downregulation of angiotensin II receptor type 1 (AT1) mRNA expression. PCI34051 treatment attenuated vascular hypertrophy by decreasing E2F3 and GATA6 mRNA expression. Vascular relaxation after PCI34051 treatment was more dependent on vascular endothelial cells and it was blocked by an NO synthase (NOS) inhibitor. In addition, NO production increased in HUVECs after PCI34051 treatment; this was decreased by the NOS inhibitor. The expression of inflammatory molecules and adhesion molecules VCAM-1 and ICAM-1 decreased in the aortas of angiotensin II-infused mice after PCI34051 administration. However, PCI34051 did not affect Nox or its regulatory subunits. CONCLUSIONS: PCI34051 lowered high blood pressure through modulation of arterial remodeling, vasoconstriction, and inflammation in an angiotensin II-induced hypertension model. We suggest that HDAC8 could be a potential therapeutic target for hypertension.